2004
DOI: 10.1113/jphysiol.2003.056101
|View full text |Cite
|
Sign up to set email alerts
|

βL–βM loop in the C‐terminal domain of G protein‐activated inwardly rectifying K+ channels is important for Gβγ subunit activation

Abstract: The activity of G protein-activated inwardly rectifying K + channels (GIRK or Kir3) is important for regulating membrane excitability in neuronal, cardiac and endocrine cells. Although G βγ subunits are known to bind the N-and C-termini of GIRK channels, the mechanism underlying G βγ activation of GIRK is not well understood. Here, we used chimeras and point mutants constructed from GIRK2 and IRK1, a G protein-insensitive inward rectifier, to determine the region within GIRK2 important for G βγ binding and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 49 publications
4
63
0
Order By: Relevance
“…Previous reports suggested a difference in alcohol and receptor activation mechanisms (4,5). In support of this finding, the rate of MTS-HE-dependent inhibition of basal currents in L344C, part of the Gβγ binding site in the βL-βM loop (28)(29)(30), was dependent on Gβγ levels, whereas MTS-HE activation of L257C channels was unaffected by varying Gβγ levels. However, alcohol-dependent (this study), Gβγ-dependent (19), and Na +z -dependent (25,(40)(41)(42) activation all involve changes in PIP 2 -GIRK affinity, suggesting a convergence of Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous reports suggested a difference in alcohol and receptor activation mechanisms (4,5). In support of this finding, the rate of MTS-HE-dependent inhibition of basal currents in L344C, part of the Gβγ binding site in the βL-βM loop (28)(29)(30), was dependent on Gβγ levels, whereas MTS-HE activation of L257C channels was unaffected by varying Gβγ levels. However, alcohol-dependent (this study), Gβγ-dependent (19), and Na +z -dependent (25,(40)(41)(42) activation all involve changes in PIP 2 -GIRK affinity, suggesting a convergence of Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Receptor-dependent Gβγ activation, however, relies on direct protein-protein interaction between GIRKs and G proteins (21,(28)(29)(30). Previous reports suggested a difference in alcohol and receptor activation mechanisms (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…1-4 indicate that activation of G␣ i subunits by GPCRs is the primary mechanism for activating TRPC4 and TRPC5. This raised the question of whether activation of the channels requires direct interaction with the G␣ i subunits, as was shown for other channels regulated by G␣ (36) and G␤␥ (33,37) subunits. To address this question, we identified the TRPC4 and TRPC5 domain that might interact with the G␣ i subunits.…”
Section: Resultsmentioning
confidence: 99%
“…Later works suggested that an intact putative site underlying A GIRK,basal is also crucial for agonist-evoked activity (58) and that a residue implicated in low affinity G␤␥ binding (57) may be involved in channel gating rather than G␤␥ binding (21,59). Thus, the issue of two types of G␤␥-binding site remains unresolved.…”
Section: Most Of the Basal Activity Of Girk Is G␤␥-dependent At Allmentioning
confidence: 99%